2023
DOI: 10.7150/ntno.78405
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green-based Glow Nanoparticles Probe for Cancer Imaging

Abstract: Indocyanine green (ICG) is one of the FDA-approved near infra-red fluorescent (NIRF) probes for cancer imaging and image-guided surgery in the clinical setting. However, the limitations of ICG include poor photostability, high concentration toxicity, short circulation time, and poor cancer cell specificity. To overcome these hurdles, we engineered a nanoconstruct composed of poly (vinyl pyrrolidone) (PVP)-indocyanine green that is cloaked self-assembled with tannic acid (termed as indocyanine green-based glow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…In addition, we investigated the in vitro cytotoxicity of free ICG (Figure S10). The results showed that the ICG concentration released by the composite was not cytotoxic, and the cell viability rate was higher than 95%, which is consistent with other previous studies . At the same time, hemolysis test (Figure b) showed that TiB 2 -QCS-ICG at different concentrations showed excellent blood compatibility after incubation with blood cells, and even at higher concentrations, the hemolysis rate was still significantly lower than the standard 5% specified in the Pharmacopoeia of the People’s Republic of China (*** p < 0.001).…”
Section: Resultssupporting
confidence: 89%
“…In addition, we investigated the in vitro cytotoxicity of free ICG (Figure S10). The results showed that the ICG concentration released by the composite was not cytotoxic, and the cell viability rate was higher than 95%, which is consistent with other previous studies . At the same time, hemolysis test (Figure b) showed that TiB 2 -QCS-ICG at different concentrations showed excellent blood compatibility after incubation with blood cells, and even at higher concentrations, the hemolysis rate was still significantly lower than the standard 5% specified in the Pharmacopoeia of the People’s Republic of China (*** p < 0.001).…”
Section: Resultssupporting
confidence: 89%
“…As previously described, chicken eggs were purchased from a local organic chicken farm and incubated at 37.8 • C, a pCO2 of 5%, and humidity calibrated to 63% [32][33][34]. First, an approximately 5 mm × 5 mm hole was cut into the eggshell using sterile scissors, followed by a second larger hole (1 cm × 1 cm) in the longitudinal side of the eggshell.…”
Section: Cam Modelmentioning
confidence: 99%
“…Due to its ability to fluorescence when stimulated with light in the infrared wavelength range, ICG is known for its use in liver function analysis [29], lymph node imaging [30], and intraoperative tumor tissue visualization [31]. Based on its composition, it interacts with macromolecular serum proteins such as albumin, known to be enriched in most cancers [32]. In clinical use, chemotherapy is applied to patients intra-venously, as we also perform in our setting.…”
Section: Introductionmentioning
confidence: 99%
“…With a short half-life of 150–180 seconds and exclusive hepatic clearance, ICG allows for continuous administration. 88…”
Section: Fluorescent Probes In the Nir Windowmentioning
confidence: 99%